FUNGSI PRODUKTIVITAS USAHATANI KAKAO RAKYAT PROVINSI SULAWESI TENGAH - Yantu Yantu; Sisfahyuni Sisfahyuni; Nilam Sari (Universitas Tadulako, 2011)
Cocoa bean is important (top) commodity especially in plantation sub-sector, and generallyin agriculture sector in Central Sulawesi Economy. The aim of the study was to identifyand to analyze the productivity function of smallholders’ cocoa farm in Central Sulawesi.The panel data analysis, i.e. fixed effect model was applied. Data used were secondarytime series data of 2000 – 2008, i.e. regency production and prices of cocoa beans, pricesof substitution commodity, prices of input factors, regency inflation, GDP and theexchange value of the currency's main export destination countries (Malaysia and USA).The secondary data was confirmed with primary data taken by purposive and unproportionalstratified random sampling techniques. The number of farmers interviewedwas 138 people. The results of the research showed that the productivity of smallholders’cocoa farm tended to be constant even decreased. Instead of having negative effect onproductivity, GDP of USA, and pesticide prices were found to have significant and positiveeffect. Besides, wage had negative effect but statistically significant. This is reasonablebecause cocoa farming requires a high level of maintenance. Finally, GDP of Malaysia hadnegative effect but statistically significant suggesting that the quality of the cocoa beanscoming from the province was low.Key Words : Cocoa farm, productivity function, and smallholders.